Electromechanical properties of calcium bismuth titanate films: A potential candidate for lead-free thin-film piezoelectrics - Simoes, A. Z.; Ramirez, M. A.; Ries, A.; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Ramesh, R. (American Institute of Physics (AIP), 2006)
CaBi4Ti4O15 (CBTi144) thin films were evaluated for use as lead-free thin-film piezoelectrics in microelectromechanical systems. The films were grown by the polymeric precursor method on (100)Pt/Ti/SiO2/Si substrates. The a/b-axis orientation of the ferroelectric film is considered to be associated with the preferred orientation of the Pt bottom electrode. The P-r and E-c were 14 mu C/cm(2) and 64 kV/cm, respectively, for a maximum applied field of 400 kV/cm. The domain structure was investigated by piezoresponse force microscopy. The film has a piezoelectric coefficient, d(33), equal to 60 pm/V and a current density of 0.7 mA/cm(2).